Proposed Marketing Strategy For E-Wallet To Increase The Growth Of Active Users (Case Study: Sap Cash) - Vina Fabiola Calista; Harimukti Wandebori (UNIVED Press, 2025)
The rapid evolution of technology has transformed various sectors, including the financial industry, where the adoption of e-wallets has become increasingly prevalent. In Indonesia, the e-wallet market has experienced significant growth, driven by a young, tech-savvy population, increased internet penetration, and the government's push towards a cashless society. SAP Cash, a new entrant in this competitive market, has struggled to convert its initial surge in total users into active, engaged customers. This research aims to address this challenge by proposing a marketing strategy to increase the growth of active users for SAP Cash.The study begins by analyzing the current consumer characteristics of SAP Cash, utilizing segmentation, targeting, and positioning (STP) to identify key consumer segments. External and internal environment analyses are conducted to understand the factors impacting SAP Cash’s performance. These analyses include an examination of the general environment, industry dynamics, competitor landscape, and the internal strengths and weaknesses of SAP Cash.The SWOT analysis reveals that while SAP Cash possesses strengths such as secure transaction processing and robust technological infrastructure, it faces weaknesses like limited brand visibility and inadequate customer support. The external environment offers opportunities, including the growing acceptance of digital payments and the potential for strategic partnerships, but also presents threats from intense competition and high bargaining power of buyers.Using the TOWS matrix, this research proposes strategic recommendations for SAP Cash. These include enhancing brand visibility through targeted digital marketing, differentiating the product with unique features, strengthening customer support, and expanding promotional activities to boost user engagement. The study also suggests leveraging strategic partnerships to broaden market reach and maintaining a forward-looking technological infrastructure to ensure scalability and security. The proposed marketing strategy is designed to increase the active user base of SAP Cash by addressing its current weaknesses and capitalizing on market opportunities. The research contributes to the field by providing a structured approach to developing and implementing a marketing strategy in a highly competitive e-wallet market. Future research could explore customer loyalty factors and the impact of emerging technologies on the e-wallet industry, providing further insights into optimizing user engagement and retention strategies for SAP Cash.